2018
DOI: 10.1245/s10434-018-6494-6
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Comparing Resection of Primary Tumor with No Surgery in Stage IV Breast Cancer at Presentation: Protocol MF07-01

Abstract: In the current trial, improvement in 36-month survival was not observed with upfront surgery for stage IV breast cancer patients. However, a longer follow-up study (median, 40 months) showed statistically significant improvement in median survival. When locoregional treatment in de novo stage IV BC is discussed with the patient as an option, practitioners must consider age, performance status, comorbidities, tumor type, and metastatic disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
290
1
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(337 citation statements)
references
References 42 publications
14
290
1
14
Order By: Relevance
“…10 One notable recent study of surgery for de novo stage 4 breast cancer is the MF07-01 trial sponsored by the Turkish Federation of the National Societies for Breast Disease. 11 In this study, the last statistical analysis in a median followup period of 40 months showed results that differed from those of the previous 36-month follow-up period, in which no difference in survival was noted between the surgery and no-surgery groups. The longer follow-up period showed a significant improvement in median overall survival of about 9 months.…”
contrasting
confidence: 50%
See 1 more Smart Citation
“…10 One notable recent study of surgery for de novo stage 4 breast cancer is the MF07-01 trial sponsored by the Turkish Federation of the National Societies for Breast Disease. 11 In this study, the last statistical analysis in a median followup period of 40 months showed results that differed from those of the previous 36-month follow-up period, in which no difference in survival was noted between the surgery and no-surgery groups. The longer follow-up period showed a significant improvement in median overall survival of about 9 months.…”
contrasting
confidence: 50%
“…In the Turkish randomized study by Soran et al 11 that investigated a group of patients randomized for no surgery, the local progression and need for palliative surgery was higher and statistically significant, with 18% of patients in the no-surgery group requiring palliation surgery. This study did not clarify how many patients lost their window of opportunity for surgery because they developed unresectable chest wall or axillary lymph node disease.…”
mentioning
confidence: 98%
“…[26] The incidence of synchronous distant metastasis in newly diagnosed breast cancer is up to 10%, [27] and the five-year survival rates for the diagnosed patients dramatically reduces from 99% to 26% due to distant metastasis. [26] The incidence of synchronous distant metastasis in newly diagnosed breast cancer is up to 10%, [27] and the five-year survival rates for the diagnosed patients dramatically reduces from 99% to 26% due to distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This trial has been critiqued for more favorable factors in the surgery arm. 8 The Tata trial reported no improvement in overall survival between the surgery versus no surgery arm for de novo Stage IV breast cancer. The results of the Tata trial need to be interpreted with caution because not only did patients have high-risk features, many patients did not receive optimal targeted therapy.…”
Section: Dear Editormentioning
confidence: 99%